(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
In the present study we have synthesized ester prodrugs (Pa-i) of Metoprolol (I) by using pthalic anhydride and derivatives of succinic and maleic anhydride. Different codrugs (COa-i) were synthesized from prodrugs of metoprolol. All the codrugs were characterized by melting point, FTIR, NMR and Mass Spectroscopy. The chemical hydrolysis of COa-i were investigated at the pH 1.2, 6.8 and 7.4. Presence of maleate, methyl maleate, dimethyl maleate and succinate group as linker were found to possess good hydrolysis when compared to that of other substitutes. Among the synthesized codrugs, COf is found to be the best one among the series.